Effect of occlusal splint on interleukin 6, malondialdehyde and 8-hydroxydeoxyguanosine levels in the synovial fluid of patients with temporomandibular disorders. Issue 12 (December 2019) - Baş, B.; Aksoy, A.; Atmaca, E.; Öz, A.A.; Kaya, Ö.; Kazan, D.; Yılmaz, E.; Kütük, N.
Abstract: The actual role of splint therapy in preventing excessive loading of the temporomandibular joint (TMJ) is still debated. Lower intra-articular pressure levels have been measured in patients wearing occlusal splints, which may also reduce oxidative stress in the articular spaces. The aim of this study was to determine whether splint therapy reduces oxidative stress and inflammation in TMJ internal derangement patients by measuring interleukin 6 (IL-6), malondialdehyde (MDA), and 8-hydroxydeoxyguanosine (8-OHdG) levels in the synovial fluid (SF). Twenty-four patients with a temporomandibular disorder (TMD) were included in the study. TMJ SF samples were obtained prior to arthrocentesis. Twelve patients used a 2-mm hard acrylic, maxillary stabilization-type splint for 3 months after arthrocentesis. Twelve patients had no treatment after the SF aspiration. Second SF samples were obtained from all patients at 3 months post arthrocentesis. IL-6, MDA, and 8-OHdG levels in the samples were evaluated. All patients showed a significant symptomatic improvement after treatment ( P < 0.005). No statistical correlation was found between the two groups concerning pre-treatment and 3-month SF levels of MDA, 8-OHdG, and IL-6. Although splint therapy was found to be successful in eliminating clinical symptoms of TMD, the results showed no beneficial effect on inflammation and oxidative stress markers in the synovial fluid.